NATO Force Planning without the Soviet Threat - Greenwood, Ted; Johnson, Stuart (1992)
in the absence of its traditional adversaries, NATO can no longer do force planning in its accustomed manner. For over 40 years, NATO force planning began by identifying military threats posed by the Soviet-led Warsaw Pact. These threats were translated into particular scenarios, which included detailed estimates of the size and quality of the forces that NATO might find arrayed against it, the length of time that NATO might have to prepare its defense after detecting hostile activities, and the strategy and tactics that the adversary might use in its offensive operations. These scenarios, in turn, were employed as a basis for sizing and structuring NATO's forces, For example, the primary scenario that NATO long used for force planning envisioned a Warsaw Pact attack against the Central Region employing some 90 to 100 divisions, preceded by an air attack against airfields, nuclear facilities, command and control installations, and other fixed targets, all with no more than 14 days' warning time. NATO might well be in for a turbulent decade on its periphery, but in the absence of identifiable adversaries, threat scenarios are no longer adequate as the basis for NATO force planning and certainly are not sufficient to win public support for national defense budgets. Yet no alternative basis for force planning has emerged. If the alliance's force planning process is to survive, a new conceptual basis will be required, one that does not rely on the outdated concept of threat scenarios but, at the same time, offers planners something more substantial than elusive risks. Conventional Military Capabilities NATO Must Counterbalance: Peacetime Force Deployments, Medium-Range Bomber Force, Forces Potentially Oriented Toward NATO's Central Region, Forces Potentially Oriented Toward North Norway, Forces Potentially Oriented Toward NATO's Southern Region, Conventional Capabilities of Turkey's Southeastern Neighbors, and Mass-Casualty Weapons within Reach of Southern Europe. Published in Parameters, v22 p27-37, Spring 1992.